Microfluidic studies on flow manipulation to assist metastasis research - Tran, Duc Quang (2017)
Cancer metastasis is initiated by cancer cells detaching from the primary tumor. This detachment process is driven by a complex combination of biophysical and biochemical effects. Among these, interstitial flow resulted from the intratumoral environment has been proven to be one of the causes assisting the directions of cell detachment and migration in tumor environment. This detachment leads to circulating tumor cells (CTCs) in vasculature or lymphatics, which can result in an uncontrollable spread of malignant tumors in the body. The appearance of CTCs is crucial for early detection of metastasis. In this study, we take advantages of microfluidics on flow manipulation to target the CTC isolation and characterize interstitial flow in a model tumor environment. Isolation of CTCs has been challenging because of their low abundance and limited timeframes of expressions of relevant cell characteristics. In this work, we devise a novel hydrodynamic mechanism to sequentially trap and isolate floating cells in biosamples. We develop a microfluidic device for the sequential isolation of floating cancer cells through a series of microsieves to obtain up to 100% trapping yield and >95% sequential isolation efficiency. Furthermore, we investigated the functional range of flow-rates for effective sequential cell isolation by taking the cell deformability into account. We verify the cell isolation ability using a human breast cancer cell line MDA-MB-231 with a perfect agreement with the microbead results. We further demonstrate that this device can be applied to isolate the largest particles from a sample containing multiple sizes of particles, revealing its possible applicability in isolation of circulating tumor cells in cancer patients’ blood. Additionally, we introduce a microfluidic platform to characterize multiple interstitial flow profiles through a tumor modelled by a cellular aggregate. Our findings demonstrate that the cellular aggregate behaves under the interstitial flow following two regimes: poroelasticity and solid plasticity, which are separated at a transient point, corresponding to fracture happened inside the cellular aggregate. We further characterize this transient point and find that the critical pressure at the transient point depended on the different loading rates of the flow. Experimental results show that the higher loading rate of the flow results in a higher critical pressure for aggregate fracture. We also develop a simplified theoretical model using poroelasticity to represent the cellular aggregate behavior within the elastic limit. These studies have shown the potential of microfluidics in application on metastasis research with the flexibility of experimental setups. Our findings contribute to metastasis early detection through high efficiency CTC isolation and better understanding in the effects of interstitial flow on cancer tumor environment.